Developing an Entrepreneurial Spirit: Case Study of Entrepreneurial Vocational School Students in Jombang - Galuh Aulia Pratiwi; Ainun Zahroh (International Journal of Economics and Management Research, 2024)
This research investigates the phenomenon of students who are active in entrepreneurship, explaining the motivations behind their involvement, the obstacles they face, as well as the development of emerging aspects of entrepreneurship and ways to improve them. Qualitative methods with a case study approach were used in this research. Data were analyzed through reduction, display and inference, with triangulation to ensure validity. Respondents consisted of students who had been running a business for at least 1 year, with a minimum turnover of 2 million per month, and were actively involved as owners in business development. Research findings show that students' main motivation for entrepreneurship is earning income for living and tuition fees, optimizing time, and the desire to strengthen themselves and contribute to society. In addition, aspects of entrepreneurship that develop include leadership, independent work, hard work, collaboration, creativity, innovation, as well as courage in making decisions and facing risks.